Evaluating the religious and cultural inclination of Dinagyang Festival and its influence of tourist visits - Aban, Ferriza Bianca; Ayalin, Louise Joevel; Beronia, Christian Jay.; Cotreras, Jules Duke.; Eriman, Danilo (2018.)
The Dinagyang Festival is one of the biggest contributors not only to the Ilonggo economy but also to the Nationhood and Identity of Ilonggos and Filipinos. With John L. Crompton's seven domains in "Motivations for Pleasure Vacation", the researchers aim to contribute to the improvement of the organization of the local festival as it continues to modernize, sophisticate through the years and change due to commercialization, generational tastes, and echnological advancements. These seven domain are believed to encompass all motivations of festival attendees that influences them to come to the festival. The domains are Equilibrium Recovery, Socialization, Novelty Seeking, Festival and Participation Learning, Family Togetherness, Spiritual Upliftment, and Cultural Exploration. In attaining the primary objective, the researchers are mainly concerned with the identification of prevalent motivational factors of Dinagyang Festival attendees. It resulted with the Cultural Exploration domain being the most prevalent factor. The researchers recommend aligning the festival activities to the needs of this factor to increase festival participants. The study is also interested in testing these variables if there exists a relationship between the seven domains and the decision to go to the next year's Dinagyang celebration. The Logistic Regression dictates that the factor Equilibrium Recovery domain possesses a positive relationship with repeat visitation. This means that those who find relief from stress in the festival are more likely to attend the next year's festival. It is recommended that organizers provide a less hectic environment in order to better enhance the Equilibrium Recovery domain and would encourage repeat visitors for next year's Dinagyang. Various tests for significant differences were also performed and would also be beneficial for the organizers of the festival. This research, its recommendations, and conclusions will be able to contribute to the development of products, services and promotion of the festival.
[Research Paper] -- [Iloilo City : UPV-CM], May 2018.